SURGICAL AND ENDOVASCULAR REVASCULARIZATION OF MYOCARDIUM IN MULTIVESSEL DISEASE - I. G. Gordeev; A. Yu. Lebedeva; N. A. Volov; I. S. Grishina; A. S. Semiokhina (Российский кардиологический журнал, 2016)
The article focuses on the comparative analysis of tactics of the rational complete and incomplete revascularizations in patients with ST elevation myocardial infarction and angina, underwent multivessel stenting and coronary bypass grafting.Patients with diffuse atherosclerotic lesion of coronary arteries are one of the most strenuous kinds of patients. The demand for revascularization of high in this group and, by the data of several authors, is up to 70% among all surgeries. This origins from the changes in demographics (population ageing) as the manifest of ischemic disease in younger age that further presents with the worse morphological substrate. The problem of optimal tactics choice (coronary bypass, endovascular revascularization, conservative strategy) of diffuse coronary atherosclerosis is still of the main topics in discussion and controversy in science.